Analysis of the Russian Olympian ski jumpers` technical fitness on the basis of information database - Zebzeyev, V. V.; Zdanovich, O. S. (Advances in Economics, Business and Management Research, 2020)
At the moment many experts, coaches and athletes in ski jumping are focused on search of the most effective ways allowing to increase quality of the training process. At the same time computer technologies are integral part of sport for a long time and are actively used in ski jumping. The aim of the research was to analyze the indicators of the Russian national team in ski jumping members technical fitness on the basis of information database. Examples of the technical fitness analysis are shown on three athletes of the Russian national team who took part in the Winter Olympic Games in Sochi. It is established that the athlete M.M. has erred in flight and contact landing phases (he has insufficiently inclined his trunk). The athlete I.H. has erred in non-contact take-off, flight and contact landing phases (insufficient extension of ankle joint and trunk bending).